Perkecambahan Biji Poliembrioni Jeruk Siam Banjar (Citrus suhuiensis L.) pada Media Tanam yang Diaplikasikan Pupuk Kotoran Ayam - Khalillurrahim, Muhammad; Aziza, Noor Laili; Jumar, Jumar (Agroekotek View, 2023)
Siamese banjar oranges are fruit commodities that are included in the type of horticultural plant that are needed by humans to fulfill balanced nutrition as a source of vitamins, minerals, and proteins that cannot be produced by the body. However its productivity is still low, so polyembryo seed are needed to pruduce apomic seeds in thr hope of increasing the productivity of banjar siam oranges in the future. Among the various alternative triggers for accelerating the growth of Banjar Siamese Orange polyembryonic seeds, one of them is the application of chicken manure because it decomposes relatively quickly, can encourange soil decomposing microbarial life and have N, P, and K to stimulate the development of plant growth. This study aimed to determine the effect to giving various doses of chiken manure on planting media for the germination of Banjar Siamese orange polyembryony seeds and to obtain the best dose of chiken manure in triggering Banjar Siamese orange polyembryonic seed germination. The research was conducted in October 2020 to November 2020 in Jl. Syekh Muhammad Arsyad Al-Banjary in village of Sungai Tuan Ulu Kec. Astambul Kab .Banjar. the study used a Factorial Completely Randomized (RAL) non factorial with five treatments and five replications, each experimental unit was repeated 10 seeds so that the total was 250 seeds. From the results of this study, it can be concluded that the application of various doses of chiken manure did not affect the germination of polyembryonic seeds, but the application of treatment gave the parameter of the percentage of germination 14 -35 days after planting and the best dose of chicken manure has not been found to trigger the germination of banjar siamese orange polyembryonic seeds. Keywords : Siamese banjar orange, Polyembrionic, Fertilizer chicken manure.